Nitrogen and carbon translocation and distribution in curcuma alismatifolia gagnep. by labelling experiment with 15N and 13C - Khuankaew T. (2014)
Curcuma alismatifolia Gagnep. rhizomes were planted on 15 May 2007. At 10 weeks after planting, at the termination of the new leaf formation stage, the plants were supplied with 15N-labeled culture solution (3.81 mM NH4+ + 8.96 mM NO3-: 10.6 atom% 15N) twice at 3 and 1 days before 13CO2 feeding. Then 13C-labeled 13CO2 (99 atom% 13C) was exposed to the shoot. The plants were harvested at four different stages of growth. The 15N and 13C abundance in each part were determined to investigate the characteristics of N and C translocation and distribution in curcuma. The total dry weights of the plant increased continuously during the termination of the new leaf formation stage (stage 1), the flowering stage (stage 2) and the rhizome storage period (stage 3) and especially rapidly increased during stage 2 to stage 3. The DW was relatively constant thereafter until the start of the dormancy period (stage 4). The total N content of the plant rapidly increased after stage 2 until stage 4. At stage 1, the total N was distributed mostly to the old storage roots, leaves and old rhizome just as the dry weight. At stage 2, the dry weights of new organs were mostly increased as well as the N content. At stage 3 and stage 4, the total N content of the new storage organs (new rhizomes and new storage roots) was highly increased, particularly in the new rhizome. The old rhizome and the old storage roots gave very low 15N and 13C in abundance. At stage 1, leaves are the main N sink and about 5.17 mg labeled N (LN) assimilated to this organ. In this stage, translocation of the newly assimilated N to the new rhizome already started. At stage 2, the distribution of LN was increased in flower and flower stalk but it was less than in the leaves that are also the main sink of N organ. At stage 3 the distribution of LN to the aboveground part organs (leaves, flowers and flower stalks) was decreased. This contrasted to the underground part organs (new rhizome, new storage roots and fibrous roots) where LN increased especially in the new rhizome. At stage 4, the 15N was mostly distributed to the storage organ (new rhizome and new storage roots) about 8.85 mg LN and 3.59 mg LN, respectively.